Role of KVKs in Jammu & Kashmir under the Plant Protection Act 2001 - Nazia Fayaz Azad; Fareed Ahmed Rafiqi; Bilal Ahmad Bhat (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
The Protection of Plant Varieties and Farmers Act,2001 is the culmination of legislative action undertaken by India to give effect to the TRIPS Agreement under the aegis of the WTO regime. This enactment is applicable in the whole of India including the state of J&K. Like in the rest of India the Ministry of Agriculture implements it through its nodal agencies known as Krishi Vigyan Kendras. This paper shall enumerate the Origin, Genesis, and mandate of Krishi Vigyan Kendras working under the aegis of the Ministry of Agriculture. It will define the role of KVKs and how farmers benefit from the schemes formulated therein. It shall illuminate the potential contribution of KVK in Kashmir Valley as an implementation machinery under the PPVFR Act 2001 and as an allied department of SKUAST-K. Needless to mention here KVKs play an important role in providing assistance and training to farmers in the shape of OFT [on-farm trials] and FLDs [front-line demonstrations] to enhance the quality of the farmer’s variety.